Verification, Model Checking, and Abstract Interpretation 15th International Conference, VMCAI 2014, San Diego, CA, USA, January 19-21, 2014, Proceedings - McMillan, Kenneth L.; Rival, Xavier; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 15th International Conference on Verification, Model Checking and Abstract Interpretation, VMCAI 2014, held in San Diego, CA, USA, in January 2013. The 25 revised full papers presented were carefully reviewed and selected from 64 submissions. The papers cover a wide range of topics including program verification, model checking, abstract interpretation and abstract domains, program synthesis, static analysis, type systems, deductive methods, program certification, debugging techniques, program transformation, optimization, hybrid and cyber-physical systems.
Program verification -- Model checking -- Abstract interpretation and abstract domains -- Program synthesis -- Static analysis -- Type systems -- Deductive methods -- Program certification -- Debugging techniques -- Program transformation -- Optimization -- Hybrid and cyber-physical systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Computer Communication Networks; Mathematical Logic and Formal Languages; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).